Novel dithiocarbamate derivatives are effective copper-dependent antimicrobials against Streptococcal species - Menghani, Sanjay V.; Sanchez-Rosario, Yamil; Pok, Chansorena; Liu, Renshuai; Gao, Feng; O’Brien, Henrik; Neubert, Miranda J.; Ochoa, Klariza; Durckel, Meredythe; Hellinger, Riley D.; Hackett, Nadia; Wang, Wei; et al. (Frontiers in Microbiology, 2023)
Despite the availability of several vaccines against multiple disease-causing strains of S. pneumoniae, the rise of antimicrobial resistance and pneumococcal disease caused by strains not covered by the vaccine creates a need for developing novel antimicrobial strategies. We found N,N-dimethyldithiocarbamate (DMDC) to be a potent copper-dependent antimicrobial against several pathogens, including Streptococcus pneumoniae. Here, we tested its efficacy against Streptococcal pathogens Streptococcus pyogenes, Streptococcus agalactiae, and Streptococcus anginosis. After confirming DMDC as broad-spectrum streptococcal antimicrobial, we then derivatized DMDC into five compounds and tested their effectiveness as copper-dependent antimicrobials against S. pneumoniae and the other streptococcal species. We found two compounds, sodium N-benzyl-N-methyldithiocarbamate and sodium N-allyl-N-methyldithiocarbamate (herein “Compound 3” and “Compound 4”), were effective against TIGR4 and further, D39 and ATCC® 6303™ (a type 3 capsular strain). Both Compound 3 and 4 increased the pneumococcal internal concentrations of copper to the same previously reported levels as with DMDC and copper treatment. However, in an in vivo murine pneumonia model, we found that Compound 3, but not Compound 4, was effective in significantly decreasing the bacterial burden in the blood and lungs of S. pneumoniae-infected mice. These derivatives also had detrimental effects on the other streptococcal species. Collectively, we demonstrate that derivatizing DMDC holds promise as potent bactericidal antibiotics against relevant streptococcal pathogens.